2003
DOI: 10.1007/s00125-003-1303-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sodium intake on blood pressure and albuminuria in Type 2 diabetic patients: the role of insulin resistance

Abstract: Aims/hypothesis. This study was done to measure the effect of Na + intake on blood pressure and albuminuria, in relation with insulin sensitivity and kidney haemodynamics, in Type 2 diabetic patients with and without microalbuminuria. Methods. Type 2 diabetic patients, 20 with microalbuminuria, 21 without, spent two consecutive 7-day periods, one on a high (250 mmol), the other on a low-Na + (20 mmol) diet. Body weight, 24-h blood pressure and albuminuria were measured at the end of each period. At the end of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
82
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(87 citation statements)
references
References 10 publications
3
82
1
1
Order By: Relevance
“…First, it might be based on compensatory hyperinsulinemia characterizing insulin resistance, which may stimulate renal sodium reabsorption, leading to volume expansion, increased adrenergic activity, and hypertension (24 -25). Worth noting, insulin resistance could contribute to greater salt sensitivity, increased glomerular pressure, and increased UAE, as recently described in type 2 diabetic patients with microalbuminuria put on a high-salt diet (26). Thus, although in our present series a correlation between insulin resistance and blood pressure was not detectable, likely because of the ongoing antihypertensive treatment, one could speculate that the difference in blood pressure level before treatment was started may have played a significant role in determining the association between UAE and insulin resistance.…”
Section: Conclusion -The Relationshipmentioning
confidence: 92%
“…First, it might be based on compensatory hyperinsulinemia characterizing insulin resistance, which may stimulate renal sodium reabsorption, leading to volume expansion, increased adrenergic activity, and hypertension (24 -25). Worth noting, insulin resistance could contribute to greater salt sensitivity, increased glomerular pressure, and increased UAE, as recently described in type 2 diabetic patients with microalbuminuria put on a high-salt diet (26). Thus, although in our present series a correlation between insulin resistance and blood pressure was not detectable, likely because of the ongoing antihypertensive treatment, one could speculate that the difference in blood pressure level before treatment was started may have played a significant role in determining the association between UAE and insulin resistance.…”
Section: Conclusion -The Relationshipmentioning
confidence: 92%
“…These corresponded to 12 studies, of which, in the studies by Houlihan et al (12,28) and McMahon and colleagues (30,31), the effects of sodium restriction on UAE and ACR were reported in separate articles, and both were considered for the meta-analysis. Because one of 12 studies reported the outcomes in a way not suitable to our analytic approach (22), only 11 studies (corresponding to 13 articles) were included in this report (12)(13)(14)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). As shown in Table 1, the meta-analysis involved 516 men and women overall from four countries.…”
Section: Characteristics Of the Studies Included In The Meta-analysismentioning
confidence: 99%
“…The participants were healthy individuals, patients with hypertension, patients with type 1 or 2 diabetes, and/or patients with normo-or microalbuminuria, established proteinuria, or a combination thereof. Most studies provided multiple cohorts (for a total of 20), including different categories of patients (25)(26)(27) or patients on different pharmacologic treatments according to a parallel arm or cross-over design (12)(13)(14)28,29,32).…”
Section: Characteristics Of the Studies Included In The Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Insulin resistance could contribute to greater salt sensitivity, increased glomerular pressure and albuminuria. [11] Insulin resistance increase the renal damage by the plasminogen activator inhibitor 1…”
Section: The Direct Impact Of Insulin Resistance On Kidneymentioning
confidence: 99%